Juegos de mesa: una estrategia metodológica para estimular las relaciones interpersonales en clases de educación física (2020)
This article describes how board game contributes to being a methodological strategy to stimulate interpersonal relationships from physical education classes. For this purpose, fifty antecedents on board games in education and interpersonal relationships in the school environment were analyzed. Of which twenty backgrounds were selected specifically for the sample, fourteen references on interpersonal relationships and six more references on board games were taken in this background review, all in the school context. The content tabs are used as instruments. The results emphasized the multiple benefits of the proper implementation of board games in education from the different authors as a result of the documentary review. Therefore, it is concluded that, by applying intentionality, objectives and relevance from planning, board games become an ideal methodological strategy to stimulate interpersonal relationships in physical education classes